Synthesis, physicochemical properties and electrochemistry of morpholine-substituted phthalocyanines - (:unkn) unknown (WORLD SCI PUBL CO INC, 2010)
The synthesis, spectroscopic and electrochemical properties of new phthalocyanines bearing four morpholine and four chloro units is reported. Two-step synthesis involved efficient nucleophilic substitution of 4,5-dichlorophthalonitrile as the key step. The free-base phthalocyanine and its several complexes have been characterized using UV-vis, IR, H-1 NMR, C-13 NMR and mass spectroscopic data. Voltammetric and spectroelectrochemical studies show that while cobalt phthalocyanine gives both metal- and ring-based, diffusion-controlled, multi-electron and reversible/quasi-reversible redox processes, other complexes give ring-based, multi-electron and reversible/quasi-reversible redox processes.
Keywords: electrochemistry; morpholine; spectroelectrochemistry; zinc; PHOTODYNAMIC THERAPY; ONE-COMPONENT; METALLOPHTHALOCYANINES; COMPLEXES; AMINATION; CATALYST; ZN(II); CO(II); AIR